Developing Halal Tourism through Stakeholder Engagement and Capacity Building - Maulana, Hafiizh; Farma, Junia; Hakim, Lukmanul; Lubis, Muharman (Jurnal Pengabdian Bakti Akademisi, 2025)
This community service activity, consisting of seminars and workshops, was conducted to address the lack of understanding and implementation of halal standards in the tourism sector, particularly among business practitioners, students, and academics. The primary objective of this initiative was to enhance human resource capacity in developing inclusive and sustainable halal tourism. The approach employed was Service-Learning, which emphasizes active collaboration between the service team, participants from diverse backgrounds, and relevant stakeholders. The activity engaged 50 participants, including culinary entrepreneurs, accommodation managers, tour guides, students, and academics. The materials presented covered key topics such as the concept of halal tourism, halal certification standards, management of Muslim-friendly destinations, and marketing strategies for halal products. Evaluation through pre-tests and post-tests revealed an average increase of 38% in participants understanding, indicating the effectiveness of the educational approach applied. Furthermore, there was an estimated 10% increase in Muslim tourist visits within six months after the activity, reflecting the positive impact of improved halal product and service quality. The involvement of students and academics also reinforced the synergy between theory and practice, fostering opportunities for applied research and innovation in halal tourism development. Challenges encountered included initial resistance from some business actors, varying levels of community readiness to adopt halal standards, and limited time availability among academic participants. These were mitigated through participatory approaches and flexible scheduling. Overall, this activity made a significant contribution to the development of sustainable halal tourism, strengthening the local economy and culture while supporting the achievement of sustainable development goals through human resource empowerment and the enhancement of the halal tourism ecosystem.